Phylogeny Reconstruction of Acetobacter Species by RAPD (Random Amplified Polymorphic DNA) Markers - Nilesh Paul3, Remya Mohanraj1*, Pranali S. Deore2 (Recent Research in Science and Technology, 2011)
RAPD (Random amplified polymorphic DNA) analysis was performed to establish the phylogenetic relationship between Acetobacter pasteurian (2522), Acetobacter xylinum (NCIM 2526). Polymorphism was analyzed based on the dendrogram of RAPD patterns using UPGMA (Unweighed Pair GroupMethod with Arithmetic Mean). RAPD analysis in our study showed that there is a 80% similarity between these bacterial strains.